2020
DOI: 10.1038/s41598-020-73972-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as systemic biomarkers to assess distress in animal models for gastrointestinal diseases

Abstract: Severity assessment of animal experiments is mainly conducted by using subjective parameters. A widely applicable biomarker to assess animal distress could contribute to an objective severity assessment in different animal models. Here, the distress of three murine animal models for gastrointestinal diseases was assessed by multiple behavioral and physiological parameters. To identify possible new biomarkers for distress 750 highly conserved microRNAs were measured in the blood plasma of mice before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 70 publications
(97 reference statements)
2
6
0
Order By: Relevance
“…Unlike body weight, FCMs and burrowing activity, the nesting score is a subjective score; however, deficits of nest building also reflect a decline in animal welfare and impaired general condition [ 30 ]. In agreement with other studies [ 24 , 25 , 27 ], most mice were highly motivated to build nests in this study, but no significant difference between each time point was observed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Unlike body weight, FCMs and burrowing activity, the nesting score is a subjective score; however, deficits of nest building also reflect a decline in animal welfare and impaired general condition [ 30 ]. In agreement with other studies [ 24 , 25 , 27 ], most mice were highly motivated to build nests in this study, but no significant difference between each time point was observed.…”
Section: Discussionsupporting
confidence: 93%
“…The advantage of faeces samples over blood samples is that they can be easily collected without additionally stressing the animals [ 26 ]. In the present research, consistent with other experimental results [ 24 , 25 , 27 ], there was a moderate increase in FCM level after the respective intervention. However, there was no statistically significant difference compared to the pre- operative phase.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lactoferrin, a laboratory biomarker, is used for clostridium difficile infection detection [ 166 ]. MicroRNAs [ 167 ], electronic-nose such as surface acoustic wave, carbon black polymer composite, carbon black polymer composite, and metal oxide semiconductors [ 168 ] have been used to identify gastrointestinal diseases. The fatty acid-binding protein has also been evaluated as a diagnostic biomarker in Gastrointestinal Diseases [ 169 ].…”
Section: Applications Of Biomarkersmentioning
confidence: 99%
“…The aim of the present exploratory and hypothesis-generating study was to identify circulating microRNAs as potential blood biomarkers with consistent differential expression across different rat models of epilepsy (amygdala kindling with focal/generalized seizures, chemical and electrical induced status epilepticus (SE) with the development of spontaneous recurrent seizures). Recent evidence suggests, for instance, a potential role for miR-132 as a general distress-associated biomarker in murine models for gastrointestinal diseases 25 . These microRNA candidates should be evaluated as potential biomarkers for identifying patients at risk to develop epilepsy-associated psychiatric comorbidities, and, in addition, to assess animal distress and cumulative severity in epilepsy models.…”
Section: Introductionmentioning
confidence: 99%